PENGARUH PENDIDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) PROVINSI MALUKU - Rosmiyati Rosmiyati; Olivia Laura Sahertian; Maria Marlyn Tetelepta (Jurnal Administrasi Terapan, 2022)
Education and training are important things to increase the knowledge and skills of employees and have an impact on one's performance at work. The purpose of this study was to determine the effect of education and training on the performance of employees of the Maluku Province Human Resources Development Agency.This research is a quantitative research, with a sample of 40 respondents. Retrieval of data using a questionnaire distributed to respondents. The analysis tool used is simple linear regression analysis with SPSS 20 software.Based on the results of data analysis, education and training have a positive effect on the performance of employees of the Maluku Provincial Human Resources Development Agency. This is evidenced by the results of the t test having a t-count value of 3.026 > t-table 2.012 and a significant value of 0.004 <0.05.Keywords : Education and training, performance